Shifting from volume to economic value in virtual water allocation problems: a proposed new framework and methodology - Lowe, Benjamin H.; Oglethorpe, David R.; Choudhary, Sonal (Elsevier, 2020)
The water footprint provided a full methodology to operationalise the virtual water concept (the volume of water used along a supply chain to produce products and services). A key theme in the water footprint literature is the efficient allocation of water resources at the global scale given the feasibility of trading water intensive commodities from water rich to water poor areas: this is an economic problem of resource allocation between alternative and competing demands, albeit with a novel international component. Moreover, given that price signals indicating relative scarcity are usually either absent or distorted for water, it is also a problem that can be seen through the lens of environmental (or non-market) valuation. However, to date environmental valuation has not been used to inform the efficient use and allocation of water within and between the different locations encompassed by international supply chains.
Keywords: water scarcity; Water footprint; value of water; Total Economic Value; stress-weighted water footprint; Benefit transfer